Boys as the ?New Disadvantaged?? The Turn in Research on Gender and Education - Kopciewicz, Lucyna (INSTED: Interdisciplinary Studies in Education & Society, 2015)
In this paper the author provides an overview of the debates ?about the boys? in United Kingdom, United States and Australia. The ways in which these debates have emerged are discussed to highlight the type of polemic which continues to inform about the moral panic surrounding the issues of boys who have acquired the status of the ?new disadvantaged?. The author explores how the issue has been portrayed as an educational crisis of the nineties and how this problem has been attributed to the impact of feminism. The most important part of the paper focuses on an anti-feminist backlash rhetoric and its impact on debates about boys? education.